PEMBINAAN GURU SEKOLAH HARI MINGGU (SHM) DI GKE BALUKON KABUPATEN PULANG PISAU - Silvia Rahmelia; Prasetiawati Prasetiawati; Agus Surya; Ventje Adri Politon (LPPM Universitas Abdurrab, 2023)
Pengabdian kepada Masyarakat as community services held by Christian Religious Education Study Program aim to improve the competence of Sunday School teachers (SHM) at GKE Balukon, Pulang Pisau District at Central Kalimantan. SHM teachers at GKE Balukon are still very limited in mastering teaching methods that are appropriate to the child's developmental level. Teachers who are in charge of teaching sometimes do not spend enough time preparing materials and teaching methods to be used, so that the activities carried out tend to be less in-depth about the message that should be conveyed regarding the word of God. Based on the analysis of the situation and conditions of the assisted communities, the formulation of the research problems includes 1) How is the competence of Sunday School teacher (SHM) at GKE Balukon?; 2) How can SHM teacher improve their competence at GKE Balukon? Through Participatory Action Research (PAR) method, the team planned action activities through coaching SHM teachers at GKE Balukon. From the results of this research in form of interviews, observations and questionnaires. It was found that the competence of SHM teachers at GKE Balukon was still weak in the aspects of professional competence and pedagogical competence. This weakness can be seen from observations during SHM where the teacher has not been able to apply the activity of applying/responding with the Bible stories conveyed. For this reason, the coaching focuses on pedagogic competence. From the results of the evaluation, SHM teachers at GKE Balukon gained new knowledge regarding the effectiveness of learning based on child's age development level and new ways of developing activities for applying/responding to Bible stories when teaching.